Heidegger on the Nature of the Work of Art - Šliogeris, Arvydas (Problemos, 1979)
The article deals with Heidegger’s views on art and on the nature of the work of art. The author reveals the German philosopher’s attempts to discard aesthetic treatment of art and to develop ontological principles for the interpretation of the work of art. These principles originally are related to Heidegger’s endeavour to resurrect so called “reflection of being”. The author maintains that Heidegger’s endeavour is in fact an attempt to resurrect religious art which he finds truly genuine. As is known, all endeavours to return the past are futile of what, as is shown in the article, Heidegger himself is aware. Therefore he is obliged to resort to an abstract idea of “recurrence” or resurrection of the “art of being” what is somewhat analogous to a kind of impotence or intellectual despair.